Influence of Indole Acetic Acid and Indole Butyric Acid on Seed Germination of Spruce - Singh, Virendra (Indian Forester, 1990)
Maximum germination was obtained in spruce when seed was treated with 36× 10-5M, 24×1O-5M and 12× 10-5M of IAA for 24,48 and 72 hours, respectively and 6×1O-5M and 12×1O-5M of IBA for 24 hours.